Tecnologias digitais da informação e da comunicação no ensino remoto emergencial: percepção dos professores do curso de administração da Universidade Estadual de Goiás - (:unkn) unknown (Universidade Estadual de Goiás, 2023)
The theme of this dissertation is digital information and communication technologies in Higher Education. The delimitation of the study of technologies in the perception of teachers in higher education, at the State University of Goiás, during the Covid-19 pandemic period, in Emergency Remote Teaching, with a time frame in the years 2020 and 2021. The bibliographic discussion includes authors such as: Pinto (1989, 2005), Castells (1999, 2003, 2010) and Levy (2003) to discuss digital culture, technology and society. And to discuss technology and education in Emergency Remote Teaching, the authors: Freire (1979, 1996, 2001, 2002 and 2019), Morin (2000 and 2011) and Kenski (2007 and 2012) and the documents published by the State University of Goiás – UEG refer to remote classes in Emergency Remote Education - ERE. This research is justified by the importance of studying teacher training in emergency remote teaching with regard to teachers' perceptions in the application of technology-mediated classes and the unexpected use of digital resources during the Covid-19 pandemic. The problem that motivated this research concerns: How do experiences with digital technologies during the period of Emergency Remote Teaching modify or expand higher education teachers' perception of technologies? The research has the general objective of analyzing the perception of teachers from the UEG Administration course in relation to pedagogical practices during the ERE period, and how technologies contributed to the holding of remote classes. This research is characterized as applied research of an exploratory nature, with a qualitative approach. The methodological procedures were the application of an online questionnaire sent by email to 97 professors, from the Administration course at the State University of Goiás. As a result, there was a greater need for the use of technological resources in higher education, which technologies have impacted positively the perception of higher education teachers in remote classes during emergency remote teaching. It is expected to contribute to studies and new strategies involving technology in Bachelor's degrees in Administration.
Digital information and communication technologies in emergency remote education: perception of teachers of the Administration course at the State University of Goiás. Master's Dissertation in Management, Education and Technology
Keywords: Tecnologias digitais; Ensino superior; Covid-19; Ensino remoto emergencial; Digital technologies; University education; Covid-19; Emergency remote teaching; CIENCIAS HUMANAS::EDUCACAO; EDUCACAO::ADMINISTRACAO EDUCACIONAL; ADMINISTRACAO EDUCACIONAL::ADMINISTRACAO DE UNIDADES EDUCATIVAS; EDUCACAO::ENSINO-APRENDIZAGEM; ENSINO-APRENDIZAGEM::AVALIACAO DA APRENDIZAGEM; ENSINO-APRENDIZAGEM::METODOS E TECNICAS DE ENSINO; ENSINO-APRENDIZAGEM::TECNOLOGIA EDUCACIONAL